NATION’S FIRST: PERAK TO DISPLAY CRIME-RELATED DATA ON CCPS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 15 August 2015 – As an outcome of a research collaboration between Universiti Sains Malaysia (USM) researchers with the Royal Malaysian Police (PDRM), the public in the state of Perak would benefit from an innovative Community Crime Prevention System (CCPS) project which enables them to be the first in receiving information concerning crimes directly from PDRM and to take precautionary measures to avoid from becoming victims, especially to street crimes.